“I’m not exotic, I’m exhausted” Africanos no Brasil, culto da elegância e consumo de luxo - Motta, Antônio (Trabalhos de Antropologia e Etnologia, 2020)
The starting point of this essay is a photographic exhibition and a performance held by a group of young Congolese men from Brazzaville (Republic of Congo) and from Kinshasa (Republic of Congo) in Brazil. What binds together these young men, their elective affinity, is the cultivation and the taste for elegance, which gains expression in a conspicuous consumption of clothing and other signs of Western fashion. Back home, these young Congolese students – who arrived in Brazil in 2008 – had a bond and identification with the Société des Ambienceurs et de Personnes Élegantes (Society of Entertainers and Elegant People), and defined themselves as sapeurs. More than an interest in the performances of these sapeurs in Brazil, in this essayI propose an interpretation of the conflicts and tensions generated by the different understandings of their presence among among the Brazilian publics, which also echoed visions of the African continent in general. It should be noted that this is the first record of the Sape in Brazil, since usually the path of a sapeur, when out of the Democratic Republic of Congo (Kinshasa) or Congo Brazzaville, leads him to Paris, its ultimate destination: the place where his way of life receives a definitive legitimation.